A Special issue on Multidisciplinary research to promote the applications in Biological sciences: Life Sciences-Biological Sciences - Dr. M. Manikandan, Guest Editor (International Journal of Life Science and Pharma Research, 2022)
The purpose of this special issue is to build a community of authors and readers to discuss the latest research and develop new ideas and research directions. The articles in this issue are led by editors who are experts in the subject and oversee the editorial process for papers. The potentially advanced special issue focuses on application of principles and problem-solving techniques of information technology in healthcare and agricultural sector. This special issue is join collaboration between Sri Krishna Arts & Science College- Autonomous & International journal of Life Science & Pharma Research. This provides a platform for the researchers to publish their innovative research findings. It also includes papers on phytochemical screening of medicinal plants and also focuses on wireless sensor networks in health care applications. The papers in this special issue are broadly divided into the applications of Microbial biotechnology, Healthcare, Agriculture, Computer technology, Data science and Artificial Intelligence.